Sustainability Assessment in Manufacturing for Effectiveness: Challenges and Opportunities - Kumar, Manish; Mani, Monto (Frontiers in Sustainability, 2022)
Manufacturing organizations continuously improve their energy, environmental, and economic performance at different manufacturing levels (products, processes, enterprise, etc.) using various assessment methodologies for visibility and a competitive market edge. Sustainability assessment has become the focus of the manufacturing performance measurement in the last decade and has triggered numerous methodological developments and adoption in practice. The assessment focus has broadened from process to enterprise-level, single to multiple parameters, fragmented to a holistic point of view, and local businesses to global sustainability and circularity. Increasing global environmental burden, resource scarcity, and human health challenges urge a shift towards effective assessment practices. This article critically reviews sustainability assessment practices in manufacturing from a methodological efficiency-effectiveness perspective. A clear distinction between efficiency and effectiveness practices has been discussed. The requirements and research challenges for effectiveness in the sustainability assessment practice in theory (academia) and practice (industry) is presented.